2015
DOI: 10.1075/dujal.4.1.03meu
|View full text |Cite
|
Sign up to set email alerts
|

English words and phrases in Dutch job advertisements

Abstract: For Marinel Gerritsen, who has pioneered research into the effects of English in advertising and who has always been a pleasure and inspiration to work with.It has been suggested that differences in mental processing affect the persuasiveness of language use. Within the Elaboration Likelihood Model framework, we examined if there were differences in the persuasiveness of English versus Dutch words in job ads depending on the way the job ads were processed, either by the central or the peripheral route. In an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In this special interest section, we bring together original, empirical work on non-nativeness in advertising for jobs (Van Meurs, Korzilius, & Bergevoet, 2015;Zenner, Speelman, & Geeraerts, 2015) and for products (Hornikx & Mulder, 2015;Raedts & Dupré, 2015). In the first paper, Zenner et al (2015) investigate factors that determine the likelihood that job advertisements published in a Belgian and a Dutch job ad magazine targeted at Dutch-speaking readers are entirely in English.…”
Section: The Current Special Interest Sectionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this special interest section, we bring together original, empirical work on non-nativeness in advertising for jobs (Van Meurs, Korzilius, & Bergevoet, 2015;Zenner, Speelman, & Geeraerts, 2015) and for products (Hornikx & Mulder, 2015;Raedts & Dupré, 2015). In the first paper, Zenner et al (2015) investigate factors that determine the likelihood that job advertisements published in a Belgian and a Dutch job ad magazine targeted at Dutch-speaking readers are entirely in English.…”
Section: The Current Special Interest Sectionmentioning
confidence: 99%
“…According to the three main determinants, jobs ads are more likely to be written entirely in English when organizations are located outside Belgium and the Netherlands, when the organizational website communication is in English, and when organizations advertise jobs in IT and the technical domain. In the second paper, Van Meurs et al (2015) focus on the effects that such use of English in the domain of job advertisements may have on readers. Earlier research has demonstrated hardly any positive effects of English compared to job ads in the receivers' own language.…”
Section: The Current Special Interest Sectionmentioning
confidence: 99%
See 1 more Smart Citation